4 good reasons why - Butler, G. ; Bourne, F. ; Green, J. W. ; Gowridge, T. ; Whitehead, A. S. ; Abell, William H. ; Pickard, J. G.; Corah, John Reginald
1938-10 1938 1930s 12 pages To the Members of the Saturday Hospital Society: Since the Society last appealed for an increased contribution, 20 years ago, the work of the Royal Infirmary has doubled and there is every indication that the demands on its services will be even greater in the future. The "4 Good Reasons" which make the present Appeal necessary are set out in this brochure. They indicate the problems now facing the Governors of the Royal Infirmary in their endeavour to maintain that high standard of efficiency which everyone must admit is essential for a Hospital serving the needs of this important industrial City, together with a big area of the County. A standstill policy in hospital work is inconceivable. Increasing demands must be met; proper accommodation must be provided; equipment must be kept up-to-date if the doctors and nurses are to do their work efficiently and to the best advantage of the patients, the majority of whom are our members and their dependents. The additional income from this Appeal will be used to build the new Casualty Department and provide up-to-date equipment in the new X-Ray Department. The task is one worthy to be undertaken by the Society, and although the sum required is a substantial one, it can be raised without individual hardship, if all do their share. The Appeal is deserving of your personal support and the Committee are confident that the response forthcoming will be generous and whole-hearted. Will you agree to increase your contribution to 3d. per week? J.R. CORAH, President. G. BUTLER, Chairman. Vice Presidents: F. BOURNE. J.W. GREEN. T. GOWDRIDGE, J.P. A. WHITEHEAD. Wm. H. ABELL, Secretary. 292/842/2/106